Rare Plankton Subcommunities Are Far More Affected by DNA Extraction Kits Than Abundant Plankton - Liu, Min; Xue, Yuanyuan; Yang, Jun (Frontiers in Microbiology, 2019)
Advances in high-throughput sequencing technologies allow a more complete study of microbial plankton community composition and diversity, especially in the rare microbial biosphere. The DNA extraction of plankton is a key step for such studies; however, little is known about its influences on the abundant or rare microbial biosphere. Our aim was to quantify the influences of different DNA extraction kits on abundant and rare plankton in the surface waters of a reservoir and provide a reference for the comparisons between microbial community studies with different extraction methods. We evaluated the influence of five common commercial kits on DNA quality, microbial community diversity and composition, and the reproducibility of methods using both 16S and 18S rRNA genes amplicon sequencing. Our data showed that results of Fast DNA Spin Kit for Soil (MPF) had higher α diversity for bacteria and high DNA quality, indicating that it is the most suitable approach for bacterioplankton diversity study. However, DNeasy Blood & Tissue Kit (QD) and QIAamp DNA Mini Kit (QQ) methods could produce results that are easier to replicate for bacteria and eukaryotes, respectively, and were more comparable between studies. The use of different DNA extraction kits had larger influence on the rare taxa compared with abundant taxa. Therefore, the comparability between studies that employed different extraction methods can be improved by removing low-abundance or less-representative OTUs. Collectively, this study provides a comprehensive assessment of the biases associated with DNA extraction for plankton communities from a freshwater reservoir. Our results may guide researchers in experimental design choices for DNA-based ecological studies in aquatic ecosystem.